Integrating Taguchi Method and Finite Element Modelling for Precision Ball Joint Manufacturing with AISI 1045 Medium Carbon Steel - Nattarawee SIripath; Naiyanut Jantepa; Sedthawatt Sucharitpwatskul; Surasak Suranuntchai (International Journal of Technology)
This study optimized the hot forging conditions for AISI 1045 medium carbon steel ball joints by integrating the Taguchi method with Finite Element Method (FEM) simulations. The research focused on three key process parameters: billet temperature (1000-1200°C), billet length (153-160 mm), and friction factor (0.15-0.64). The analysis of Variance (ANOVA) identified billet temperature and friction factor as the most influential parameters, accounting for over 96% of the variation in forging loads. Optimal forging conditions were determined as a billet temperature of 1200°C, billet length of 153 mm, and friction factor of 0.15. The linear regression models exhibited high predictive accuracy, with R² values of 0.978 and 0.988 for maximum preforming and finishing loads, respectively. FEM simulations incorporating the Johnson-Mehl-Avrami-Kolmogorov (JMAK) model effectively predicted the microstructural evolution with grain sizes ranging from 5.10 to 41.22 ?m, showing a mean deviation of 15.51% from experimental measurements. The simulations also accurately predicted the pearlite phase transformation, achieving a 37-42% pearlite volume fraction with only a 5.33% error and tensile strength distributions ranging from 642.04 to 642.12 MPa. Experimental validation confirmed defect-free die cavity filling, with FEM simulations and predictive models showing satisfactory agreement with experimental forming loads for both preforming and finishing stages. This integrated approach offers a robust framework for optimizing complex forging processes, ensuring consistent product quality, and minimizing material waste.